a - Fina Afriani Putri; Fatni Mufit (Postgraduate, University of Mataram, 2023)
The importance of scientific skills in the future and Indonesia's low ranking internationally have not escaped the government's attention, as evidenced by the existence of the National Literacy Movement Program. In this regard, a study was conducted which aimed to describe data on students' initial abilities in scientific literacy in the material of work and energy as well as momentum and impulse. This research is part of a preliminary study of research into the development of teaching materials to improve students' scientific literacy skills. The total sample consisted of 100 students from three SMAN schools in the city of Padang with the categories low, medium and high based on UTBK scores in 2023. The research sampling technique was cluster random sampling. The scientific literacy ability test consists of 10 complex multiple choice questions. The results of the analysis prove that the students' initial level of ability in scientific literacy in the material of work and energy as well as momentum and impulse is included in the very low category, with an average percentage of 35.4% in the context aspect, an average percentage of 35.6% in the content aspect, and an average percentage of 35.3% in the competency aspect.